Characterization and immunomodulatory effect of an alkali-extracted galactomannan from Morchella esculenta. (15th February 2022) - Zhang, Nan-Nan; Ma, He; Zhang, Zhong-Fei; Zhang, Wen-Na; Chen, Lei; Pan, Wen-Juan; Wu, Qing-Xi; Lu, Yong-Ming; Chen, Yan
Abstract: In our continuous exploration for bioactive polysaccharides, a novel polysaccharide FMP-2 was isolated and purified from the fruiting bodies of Morchella esculenta by alkali-assisted extraction. FMP-2 had an average molecular weight of 1.09 × 10 6  Da and contained mannose, glucuronic acid, glucose, galactose, and arabinose in a molar ratio of 4.10:0.22:1.00:5.75:0.44. The backbone of FMP-2 mainly consisted of 1, 2- α -D-Gal p, 1, 6- α -D-Gal p, and 1, 4- α -D-Man p, with branches of 1, 4, 6- α -D-Man p and 1, 2, 6- α -D-Gal p . FMP-2 can stimulate phagocytosis and promote the secretion of NO, ROS, and cytokines like IL-6, IL-1 β, and TNF- α in RAW264.7 cells ranging from 25 to 400 μg/mL. FMP-2 had great repairing effect on the immune injury of zebrafish induced by chloramphenicol. The phagocytosis ability of zebrafish macrophages and the proliferation of neutrophils can be greatly enhanced by polysaccharide FMP-2 with concentrations from 50 to 200 μg/mL. These findings suggest that FMP-2 might be used as a potential immunomodulator in the food and pharmaceutical industries. Graphical abstract: Unlabelled Image